2012
DOI: 10.4236/ajps.2012.35082
|View full text |Cite
|
Sign up to set email alerts
|

Plant Composition of Skuas Nests at Hennequin Point, King George Island, Antarctica

Abstract: We investigate the plant composition in the Skuas nest at Hennequin Point, located in the Admiralty Bay Area, King George Island, Antarctica. Sample of 61 activity nests were analyzed. 21 plant and lichenized fungi species were found in the nest composition, being the mosses Sanionia uncinata (Hedw.) Loeske and Polytrichastrum alpinum (Hedw.) G. S. Smith the most frequent species found in the Skuas nests. Usnea antarctica Du Rietz was the most frequent lichen and the grass Deschampsia antarctica Desv was the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Some studies have reported that Antarctic sea birds ( Catharacta spp. and Larus dominicanus ) use D. antarctica communities for breeding (Albuquerque et al 2012; Parnikoza et al 2012). However, this should increase N availability as well by guano addition, and the highest levels of N were not found under this species.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that Antarctic sea birds ( Catharacta spp. and Larus dominicanus ) use D. antarctica communities for breeding (Albuquerque et al 2012; Parnikoza et al 2012). However, this should increase N availability as well by guano addition, and the highest levels of N were not found under this species.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that saxicolous species found growing on the whale vertebrae were not found on the surrounding pebbles on the beach. Plant growth limited to bones is probably related to the rich mineral content of the whale bones and the establishment of bird foraging/resting areas around the intertidal zone (Albuquerque et al, 2012). Skuas and sea gulls nesting near the whale bones could increase nutrient composition, mainly nitrates derived from guano.…”
Section: Discussionmentioning
confidence: 99%
“…However, their occurrence and development are restricted by local environmental conditions, such as substratum instability, rock type and surface texture, permanent shading from direct solar radiation, excessive exposure to strong and abrasive wind action, mineral particles and ice crystals and, in the close proximity of bird colonies, the impact of disturbance and toxic levels of certain chemical elements (Smith, 2007). Some species are abundant and form distinct communities in habitats receiving nutrient enrichment (especially from nitrogenous compounds in meltwater run-off and in aerosol form) from seabird colonies (Jablonski, 1986); although lichens may develop dense stands even in some nutrient-deficient habitats (Albuquerque et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are, of course, birds that use other materials, such as rocks, in the case of giant petrels and penguins (Figure 13), mud with algae as is the case of Phalacrocorax atriceps, etc. [53]…”
Section: Mosses and Hepaticsmentioning
confidence: 99%